2016
DOI: 10.15537/smj.2016.11.14557
|View full text |Cite
|
Sign up to set email alerts
|

Alfentanil versus ketamine combined with propofol for sedation during upper gastrointestinal system endoscopy in morbidly obese patients

Abstract: Objectives:To observe the effects of both propofol/alfentanil and propofol/ketamine on sedation during upper gastrointestinal system endoscopy in morbidly obese patients (UGSEMOP).Methods:In a prospective, double-blinded, randomized clinical study, 52 patients scheduled for UGSEMOP were assigned to either group A (n=26; 10 µg/kg intravenous [IV] alfentanil) or group K (n=26; 0.5 mg/kg IV ketamine). Each patient was administered 0.7 mg/kg propofol for induction. If it was needed, the patients were administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Gastroscopy is a noninvasive operation, but gastroscopy without sedation/anesthesia often causes adverse reactions such as nausea, vomiting, and coughing ( Meng et al, 2016 ). To provide patients with comfortable (i.e., painless) gastroscopy, propofol is considered the best sedation anesthetic according to many studies ( Smith et al, 1994 ; Ellett, 2010 ; Olofsen et al, 2010 ; LaPierre et al, 2012 ; Zhang et al, 2014 ; Kılıc et al, 2016 ; Ma et al, 2016 ). Propofol has no analgesic effect; so, propofol combined with opioids can alleviate the cardiovascular response, reduce noxious stimuli, and reduce the dose of propofol ( LaPierre et al, 2012 ; Anesthesiology Branch of Chinese Medical Association, Digestive Endoscopy Branch of Chinese Medical Association, 2014 ; Zhang et al, 2014 ; Kılıc et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastroscopy is a noninvasive operation, but gastroscopy without sedation/anesthesia often causes adverse reactions such as nausea, vomiting, and coughing ( Meng et al, 2016 ). To provide patients with comfortable (i.e., painless) gastroscopy, propofol is considered the best sedation anesthetic according to many studies ( Smith et al, 1994 ; Ellett, 2010 ; Olofsen et al, 2010 ; LaPierre et al, 2012 ; Zhang et al, 2014 ; Kılıc et al, 2016 ; Ma et al, 2016 ). Propofol has no analgesic effect; so, propofol combined with opioids can alleviate the cardiovascular response, reduce noxious stimuli, and reduce the dose of propofol ( LaPierre et al, 2012 ; Anesthesiology Branch of Chinese Medical Association, Digestive Endoscopy Branch of Chinese Medical Association, 2014 ; Zhang et al, 2014 ; Kılıc et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…To provide patients with comfortable (i.e., painless) gastroscopy, propofol is considered the best sedation anesthetic according to many studies ( Smith et al, 1994 ; Ellett, 2010 ; Olofsen et al, 2010 ; LaPierre et al, 2012 ; Zhang et al, 2014 ; Kılıc et al, 2016 ; Ma et al, 2016 ). Propofol has no analgesic effect; so, propofol combined with opioids can alleviate the cardiovascular response, reduce noxious stimuli, and reduce the dose of propofol ( LaPierre et al, 2012 ; Anesthesiology Branch of Chinese Medical Association, Digestive Endoscopy Branch of Chinese Medical Association, 2014 ; Zhang et al, 2014 ; Kılıc et al, 2016 ). Too large a dose of opioid drugs could inhibit the patients’ respiratory and circulatory systems, and too small a dose of opioid drugs could not help patients to finish a gastroscope placement.…”
Section: Introductionmentioning
confidence: 99%
“…18 For sedation during colonoscopy, gastrointestinal system endoscopy and hip fracture surgery, alfentanil and propofol have been extensively utilized. [19][20][21] However, there are cardiac side effects associated with a combination of alfentanil and propofol, such as systolic hypotension, bradycardia and hypoxemia, 22 which should not be ignored. A recent published research showed that moderate sedation induced by remimazolam and alfentanil caused less adverse events compared to propofol-alfentanil combination during third molar extraction.…”
Section: Introductionmentioning
confidence: 99%